An in vitro study of wound healing activity of ficus deltoidea leaves extract - Wan Mustaffa, Nurul Ain Aqilla (2015)
Ficus deltoidea (Mas Cotek) is one of the popular herbs that has been used traditionally to alleviate illnesses. The present study aimed to investigate the in vitro wound healing activity of F. deltoidea leaf extract on skin cell. Cell proliferative and migration assay were done on the Human Skin Fibroblast cell (HSF 1184) which were treated with different concentrations of F. deltoidea leaf extract. The data of wound closure were collected at time intervals of 0, 6, 12 and 24 hours and analyzed using ImageJ™ software. MTT assay revealed that the F. deltoidea leaf extract could induce cell proliferation at a dose dependent manner. F. deltoidea leaf extract significantly accelerated the wound closure process in comparison to cells treated with ascorbic acid and untreated cells in scratch assay. Following 24 hours of incubation, cells treated with 50 mg/mL of F. deltoidea leaf extract showed remarkable proliferative and wound closure effect with 143.67% and 5.96%, respectively as compared to other concentrations. Collectively, these findings suggested that F. deltoidea leaf extract possesses wound healing potential and may be useful for the development of efficient wound healing drug.